Sustainability Transformation for Healthcare Facilities Following Net Zero Model - ElMitainy, Esraa (AUC Knowledge Fountain, 2025)
The healthcare industry is a field undergoing huge development. Focused on SDG 3 “Good Health and Well-being”, the healthcare industry, as the main health service provider, was marked by experts as a sector that should lead sustainable development by example. The current work aims to formulate a sustainability rating system for new and existing healthcare facilities to encourage the Egyptian healthcare industry to move towards sustainability according to net zero concepts. Additionally, the transition to net zero waste is investigated though experimental work to test the possibility of utilizing sterilized medical waste in cement-based bricks. The rating system starts with two general prerequisites for management, and covers three specialty sections energy, water and habitat. Each section has prerequisites and credit awardable implementation actions that are awardable upon fulfilment of requirements. Additionally, an approaching net zero assessment system is formulated for energy, water, waste and GHGs emissions, where a baseline benchmark should be calculated and subsequent targeted savings achieved. experimental work to assist the approach to net zero waste was undertaken, where shredder/autoclave waste, and bottom ash from medical waste incinerators are used to fabricate cement bricks. Also, marble and granite powder are tested as additives to increase the brick strength. Shredded/autoclaved waste was agglomerated before utilization, and the compressive strength test concluded that the 10% agglomerated waste with 10% marble powder additive showed satisfactory results compared to ASTM C55 requirement. While the bottom ash sample performing closest to target was 15% bottom ash, with 5% marble and only 10% cement.